PENGANGKATAN ANAK OLEH ORANG YANG TIDAK MELAKUKAN PERKAWINAN DALAM SISTEM HUKUM PERDATA NASIONAL - Glad Mauraina; Angel Pratiwi; Dian Purnama (Cepalo, 2021)
Adoption is carried out by a legally married couple and could also be done by someone who does not want to build a household but still wants to have children as successors and who would take care of them in the future as a single parent. Article 10 paragraph (3) of the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 110/HUK/2009 concerning Child Adoption Requirements states that child adoption through a childcare institution could be carried out firstly by a prospective foster parent. Prospective Foster Parents have been legally married for a minimum of five years, as stated in Article 20 letter e of the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 110/HUK/2009. In this research journal, we would discuss the issue of Child Adoption by Non-Marriage Person. This study focuses on normative legal research that examines the content of legislation. This legal research was conducted with two approaches consisting of a statutory approach and a conceptual approach. Researchers would find ideas that provide legal understanding, legal concepts, and legal principles. This research concludes that adoption could be carried out by married couples and non-married person/single parent. It is referred to Government Regulation Number 54 of 2007 concerning Adoption of Children. This regulation is reinforced by the issuance of Circular Letter of the Supreme Court (SEMA) Number 6 of 1983 explaining that it is possible for Indonesian citizens who are unmarried, have been married, or a single parent, to adopt a child.